Twitter Sentiment Analysis on Halal Cosmetics - Siti Maysyaroh; Aam Slamet Rusydiana (Islamic Marketing Review, 2023)
This study aims to analyze sentiments related to halal cosmetic products through data taken from the Twitter social media platform. The method used in this research is sentiment analysis using a Python library known as VADER (Valence Aware Dictionary and Sentiment Reasoner). The data retrieved includes tweets with keywords related to "halal cosmetics" in the period January 1, 2019 to March 28, 2023. The results of this sentiment analysis reveal that the majority of sentiments related to halal cosmetics are positive, with a percentage of around 56.8%. Furthermore, about 36.1% of the detected sentiments are neutral, indicating that most consumers have a neutral view towards halal cosmetic products. Negative sentiments have a percentage of 7.1%, indicating that there is a small percentage of users or consumers who may have problems or negative experiences related to these products. The results of this study provide a better understanding of how consumers respond to halal cosmetic products on the social media platform Twitter, as well as identify opportunities and challenges within this market. The implications of these findings can help manufacturers and stakeholders in the halal cosmetics industry to improve consumer understanding, address emerging issues, and support the growth of this rapidly evolving industry.